(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
The research focuses on the adaptation of greenhouses for farming, emphasising its positive feedback as a feasible and sustainable option for year-round crop cultivation. The research involves a system that utilises sensors connected to a microcontroller to monitor greenhouse conditions. The sensors measure temperature, humidity, soil moisture, light intensity, and water levels. The system is powered by AC to DC supply, with additional features like a fan to cool the environment and a bulb responding to natural light intensity. The collected data is sent to a webpage for remote monitoring through the Serial Peripheral Interface Flash File System (SPIFFS). The study encompasses two main aspects: sensing and regulation, and transmitting real-time data for remote monitoring.